Older adults’ experiences of ehealth in health and social care - Mielonen, Jukka; Kuusisto, Hanna; Kinnunen, Ulla-Mari; Kemppi, Anssi; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2023)
Using the Unified Theory of Technology Acceptance (UTAUT) model as a framework for this study, the aim was to describe how older adults assess digital services in terms of ease of use and quality in health and social care and how often those services are offered. Further, the aim was to describe how older adults receive support for service use, focusing on people aged 65 and over. A structured web-based questionnaire was used for data collection. The data (N=978) was analysed by quantitative statistical analysis. Most of the respondents found the digital services of health and social care easy to use. The function of the services was considered understandable. Respondents also felt that they could find the necessary information about the services. For the most part, they received service use help from their children or grandchildren. However, the role of health and social services professionals was less important. According to our findings, older adults received minimal support from health and social care professionals or employees in third sector organizations. Although, most respondents (70 %) needed support when using digital services. In the future, health and social care service providers should invest in increased digital services. In conclusion, we found that older citizens know how to use digital services in the health and social care context and they receive adequate help from their relatives in using them.